APPLICATION FUNGTIONAL AND ELEGANT APPROACH AT MASJID FATAHILLAH DESIGN BULAK RANTAI AT JAKARTA TIMUR - Rita Laksmitasari Rahayu (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2022)
The location of the Fatahillah Mosque in the Bulak Chain housing complex, East Jakarta. The age of the Fatahillah Mosque building is quite old, which is 40 years. Major repairs of buildings are unavoidable. With increasing age, the Fatahillah Mosque is increasingly used by the congregation, especially on Muslim holidays. Another renovation goal is the adjustment of the Qibla direction based on guidelines from the Indonesian Ministry of Religion. On the design concept, the Architect as a team from Community Service conducted a study, using four Islamic concepts, namely Ijtihad, Taqlid, Not Exaggerated, and Rational. The design approach method is functional and elegant. Benefits for partners, Fatahillah Mosque is a mosque that has security, comfort, and adds solemnity to the congregation. Qibla direction that is in accordance with the guidelines of the Indonesian Ministry of Religion. Fatahillah Mosque was redesigned with renovation properties from 300 worshipers to 600 worshipers with 3 floors. The ground floor is a multi-purpose room, while the second and third floors are prayer rooms. This new design will increase the comfort and solemnity of the congregation in worship. Architects carry out the design and socialization stages to mosque managers in a careful, structured, systematic manner. The problem seeking and problem solving stages are the key to the success of a design. State of the art in Community Service is the architect choosing and applying the concept of the Four Islamic concept design at the Fatahillah Bulak Chain Mosque, to get the right results according to the context and existing problems.